Development Of E-Learning using Moodle as Online Course Media on Private Sean Institute - Hasugian, Paska Marto; Sijabat, Petti Indrayati (Login : Jurnal Teknologi Komputer, 2023)
Today's technological developments have developed rapidly and have become an integral part of supporting the smooth running of activities or daily activities in government agencies, marketing, and even informal and non-formal education. The purpose of this research is to develop e-learning in support of online course activities given the current conditions during the pandemic, which resulted in activities being carried out from home or with the term Work From Home (WFH). From Leni Zuliana's research, she has researched the topic of analyzing the use of e-learning and found that there was a significant increase when using the media, with the calculation of the media expert's assessment being said to be very feasible with an overall average of 100% and the evaluation of material experts in every conceivable category. With an overall mean of 95.4%. This research aims to produce e-learning, which can be used as a medium for online course learning. Some of the work steps used to make e-learning are ensuring problems with the object under study, collecting data, developing applications, testing, and implementing media. The content on e-learning is created with several features, namely 1) uploading course material in a specific form, pdf, PowerPoint and video 2) making daily questions and assessing and returning answer papers 3) real-time video conference facilities with zoom or with supporting facilities and other supporting activities that can be included in e-learning.